Association of remnant cholesterol and non-high density lipoprotein cholesterol with risk of cardiovascular mortality among US general population. Issue 8 (August 2022) - Cheang, Iokfai; Zhu, Xu; Lu, Xinyi; Shi, Shi; Tang, Yuan; Yue, Xin; Liao, Shengen; Yao, Wenming; Zhou, Yanli; Zhang, Haifeng; Li, Yanxiu; Li, Xinli
Abstract: Background: There are strong association between remnant cholesterol (RC)/non-high density lipoprotein cholesterol (NHDL-C) and increase cardiovascular (CV) risk. The aim of present study was to investigate the association between target lipid parameters (RC and NHDL-C) and the risk of CV mortality in general population. Methods: Data set from an open database—National Health and Nutrition Examination Surveys (NHANES) 2003–2014 were extracted (n = 14992). Kaplan-Meier, multivariable COX regression, and restricted cubic spline (RCS) parameters. Results: Compared to the lowest quartile, RC (adjusted hazard ratio [HR] = 1.63 95%CI 1.05–2.52, P for trend = 0.037) and triglycerides (TG: Model 3: HR = 1.69 95%CI 1.10–2.60, P for trend = 0.049) in the highest quartile were independently associated with the increased cardiovascular mortality, while NHDL-C and apolipoprotein B (ApoB) in adjusted models did not show association (P for trend >0.05). In addition, RCS regression demonstrated that RC (P for nonlinearity = 0.011) and TG (P for nonlinearity = 0.010) levels had a similar J-shape association with CV mortality. Threshold effect analysis showed that when RC ≤ 29.3 mg/dL, the level of RC and CV mortality risk were positively correlated. Conclusions: Our findings suggest high RC levels are associated with an increased risk of CV mortality, which support that the integration of TG-rich lipoproteins parameters in risk assessment might optimize the identification and management of selected population. Abstract : Lipid; Remnant cholesterol; Non-high density lipoprotein cholesterol; Cardiovascular mortality; Risk assessment.